TO SCREEN THE CHILDREN AGED 4 MONTHS TO 15 YEARS FOR POSSIBLE UTI AND POINT PREVALENCE ON THE BASIS OF URINE MICROSCOPY AND/OR URINE DIPSTICK IN FEVER WITHOUT A FOCUS IN A PERIPHERAL HOSPITAL - Lone, Rais Ahmad; Shiekh, Hafeezullah; MAJEED, NOUSHEEN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The aim of the study was to screen the children aged 4 months–15 years for possible urinary tract infection (UTI) and point prevalence on the basis of urine microscopy and/or urine dipstick in fever without a focus in a peripheral hospital. Methods: This was a hospital-based outpatient study conducted in the pediatric patients of district hospital Shopian between January 2021 and December 2021. A total of 9000 children were seen but most had (or developed) a focus. Only 180 patients did not develop any focus and were the actual subjects subjected to urine microscopy/urine dipstick to identify the possible UTI. Results: Of the 9000 children seen 8820 patients had (or developed) a focus. One hundred and eighty patients did not develop any focus and corresponded to 2% with 74 (41.111%) male and 106 (58.888%) female children of which 62 had positive urine microscopy/dipstick corresponding to 0.6889%, with 24 (38.7%) male and 38 (61.3%) female suggesting a point prevalence of 0.6889%. Conclusion: Urine microscopy and/or urine dipstick of a clean voided urine specimen may reasonably be used to rule out UTI and excluded from further confirmatory invasive urine culture. Similarly positive tests could be used to rule in UTI and proceed for further investigation.